Stick-climb-slip induced damage mode in Cu/Si(100) thin films deposited by modulated pulsed power magnetron sputtering during scratch. (April 2020) - Meng, D.; Li, Y.G.; Jiang, Z.T.; Lei, M.K.
Abstract: Stick-climb-slip induced damage mode during a scratch test was studied in the Cu/Si(100) thin films deposited by modulated pulsed power magnetron sputtering, to characterize the adhesion of the thin films. The two typical periodical morphologies were observed on the scratch tracks after first edge chipping of the Cu/Si(100) thin films. The first type was a series of wave-like traces outside the scratch track, and another was the periodical semi-circular deformation characteristic within the scratch track. Finite element method (FEM) was used to analyze the stress-strain response in the Cu/Si(100) thin films for the moved scratch tip under the applied load. It was found that the concentrations of maximum principal stress in zones A, B and C were responsible to the formation of groove pileups accompanied by the periodical accumulation and release of the strain energy with a contact force periodically fluctuated. The scratched tip in the ductile Cu/Si(100) thin films would repeatedly experience the forward pileups along thinning and growing trace, and gradually climb up and then drop down with a sudden movement. The stick-climb-slip induced damage modes of the thin films can provide the evaluation of the critical loads in the scratch test. Highlights: Two periodical morphologies were observed on the scratch tracks for Cu thin films. The morphologies were controlled by maximum principal stress in zone A, B and C. A climb process of the moved tip in the stick-slip stage during a fluctuation period. The climb process of the tip was inferred from the calculative tip contact forces. The stick-climb-slip induced damage modes can provide the evaluation of L c.